2010
DOI: 10.2478/v10042-010-0030-2
|View full text |Cite
|
Sign up to set email alerts
|

The importance of preoperative elevated serum levels of CEA and CA15-3 in patients with breast cancer in predicting its histological type.

Abstract: Material and methodsTumour samples. A total of 428 patients were treated at The Department of Surgery of Wroclaw Medical University from 2005 to 2008 due to the diagnosis of breast cancer. All of them had their preoperative CA 15-3 and CEA serum concentrations measured. In all patients tumours were invasive cancers in stages I-III, and the mean age of patients was 52.5 years (range 24-83 years). All the patients in the study were women and 54.5% of them were postmenopausal.Tumour markers. Studied tumour marker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 11 publications
(12 reference statements)
2
9
0
Order By: Relevance
“…In the present study, VEGF was measured from the serum. 31,32 In our study also CA 15.3 levels showed a direct correlation with both tumour size (p 5 0?008) and stage of the disease (p 5 0?001) in all patients. 25 Some studies showed that platelet-poor plasma reflects more accurate tumour progression 26 whereas others found that serum VEGF gives a better indication of tumour progression.…”
Section: Discussionsupporting
confidence: 68%
“…In the present study, VEGF was measured from the serum. 31,32 In our study also CA 15.3 levels showed a direct correlation with both tumour size (p 5 0?008) and stage of the disease (p 5 0?001) in all patients. 25 Some studies showed that platelet-poor plasma reflects more accurate tumour progression 26 whereas others found that serum VEGF gives a better indication of tumour progression.…”
Section: Discussionsupporting
confidence: 68%
“…CA15-3 and CEA have been reported to be associated with clinicopathological parameters [ 68 ]. Both the CA15-3 and CEA levels were elevated with a larger tumor size, positive lymph node metastasis, and advanced TNM stage.…”
Section: Discussionmentioning
confidence: 99%
“…Despite extensive study of CEA and CA15-3, their utility as breast cancer markers remains unclear (10). The majority of tumor markers are used for early diagnosis, determining prognosis, monitoring therapeutic efficacy and follow-up subsequent to therapy (11)(12)(13)(14)(15)(16). However, CEA and CA15-3 are unsuitable for early detection due to their low expression and lack of sensitivity in breast cancer (11,17).…”
Section: Elevation Of Serum Cea and Ca15-3 Levels During Antitumor Thmentioning
confidence: 99%